Social choice, nondeterminacy, and public reasoning - (:unkn) unknown (Saint Louis University, 2021)
This article presents an approach to how to make reasonable social choices when independent criteria (e.g., prioritarianism, religious freedom) fail to fully determine what to do. The article outlines different explanations of why independent criteria sometimes fail to fully determine what to do and illustrates how they can still be used to eliminate ineligible alternatives, but it is argued that the independent criteria cannot ground a reasonable social choice in these situations. To complement independent criteria when they fail to fully determine what to do, it is suggested that society must engage in public deliberation by way of generating new reasons that can determine how to rank the alternatives. It is suggested that the approach to social choice presented here reveals a way of accepting the relevance of independent criteria for social choice without letting go of the idea that the attitudes of affected parties matter. © 2021 Anders Herlitz